The art of occlusal and esthetic waxing - Abdalla, Rowida ([S.l.] : Quintessence Publishing Co, Inc., 2019)
This book is a concise but comprehensive guide for understanding the basic principles of occlusion and esthetics that are necessary to perfect wax-ups on mounted casts. The author defines important occlusal terminology and describes tooth morphology with a focus on how these features affect function. The esthetic principles that affect smile design and are important for achieving harmony are also discussed. The second half of this book provides an overview of the waxing armamentarium and stepby-step waxing instructions for maxillary and mandibular posterior teeth in occlusion as well as esthetic wax-ups. With useful photographs and illustrations throughout, The Art of Occlusal and Esthetic Waxing has the practical information that will help readers perfect their wax-ups and understand the significance of morphologic features on proper function.
The art of occlusal and esthetic waxing -- Dedication -- Contents -- Preface -- Chapter 1. Introduction to Occlusion -- Chapter 2. Principles of Esthetics -- Chapter 3. The Dental Articulator -- Chapter 4. Waxing Mandibular Posterior Teeth in Occlusion -- Chapter 5. Waxing Maxillary Posterior Teeth in Occlusion -- Chapter 6. Esthetic Wax-Ups -- References.
Includes bibliographical references and index.
Keywords: Inlay Casting Wax; Dental Impression Technique; Dental Occlusion; Tooth -- anatomy & histology; Waxes